Height Uniformity Simulation and Experimental Study of Electroplating Gold Bump for 2.5D/3D Integrated Packaging - Wenchao Tian; Zhao Li; Yongkun Wang; Guoguang Zhang (Micromachines, 2022)
With the rapid development of nano/micro technology for commercial electronics, the typical interconnection method could not satisfy the high power-density packaging requirement. The 2.5D/3D integrated packaging was seen as a promising technology for nano/micro systems. The gold (Au) bump was the frequently used bonding method for these systems because of its excellent thermal, electric, and mechanical performance. However, relatively little work has been performed to analyze its height uniformity. In this study, the simulation and experimental methods were used to analyze the Au bump height uniformity. Firstly, the electroplating process of Au bump under different flow field parameters was simulated by COMSOL software. The simulated results indicated that the Au+ concentration polarization was the significant reason that caused the non-uniform distribution of Au bump along the wafer radius. Meanwhile, the flow field parameters, such as inlet diameter, inlet flow, titanium (Ti), wire mesh height, and Ti wire mesh density, were optimized, and their values were 20 mm, 20 L/min, 12 mm, and 50%, respectively. Subsequently, the Au bump height uniformity under different current densities was analyzed through an experimental method based on these flow field parameters. The experimental results showed that the increases of current density would decrease the Au bump height uniformity. When the current density was 0.2 A/dm2, the average height, range, and deviance values of Au bump were 9.04 μm, 1.33 μm, and 0.43 μm, respectively, which could reach the requirement of high density and precision for 2.5D/3D integrated packaging.